Rancang Bangun Prototype Pencetak Biobriket dengan Sistem Hidrolik - Putri, Intan Dwi; Maharani, Sania Azizah; NH, Harmiwati; Nirmala, Dyah (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Briquettes are an alternative biomass-based fuel with the potential to reduce fossil fuel consumption. This study aims to design and develop a hydraulic system-based briquette press prototype to improve production efficiency and briquette quality. The hydraulic system was chosen for its ability to provide uniform pressure, resulting in briquettes with consistent dimensions and density. The construction process utilized materials such as galvanized hollow steel, angle iron, and hydraulic jacks. The press design includes 35 cubic molds with dimensions of 3x3x3 cm. This study evaluated the performance of the device in producing briquettes from sawdust charcoal using varying adhesive ratios and drying times. The results showed that the average briquette density reached 0.8 g/cm³, meeting international standards (0.46–1.2 g/cm³). The optimal ratio of charcoal to adhesive was 1.5:1, with an optimal drying time of 4 hours, producing high-quality briquettes with moisture content, volatile matter, and ash content meeting SNI standards. Compression strength tests also demonstrated adequate values, conforming to BNJ 01-6235-2000 standards.This briquette press has proven effective in producing high-quality briquettes, making it a promising innovation to support the production of environmentally friendly alternative fuels.